A thiosemicarbazone based chemo and fluorogenic sensor for Zn2+ with CHEF and ESIPT behaviour: computational studies and cell imaging application. Issue 14 (27th January 2016) - Bhowmick, Rahul; Alam, Rabiul; Mistri, Tarun; Das, Kalyan Kumar; Katarkar, Atul; Chaudhuri, Keya; Ali, Mahammad
Abstract : A novel diformyl- p -cresol (DFC )–thiosemicarbazide (TS ) – based turn-on dual sensor that enables to determine, for the first time, the stepwise formation constants. Abstract : We report herein the development of a novel, diformyl- p -cresol (DFC )–thiosemicarbazide (TS ) based sensor (DFC–TS ) that selectively and sensitively recognizes Zn 2+ by both UV-Vis and fluorescence methods. The gradual addition of Zn 2+ to a solution of the ligand developed a new absorption band at 430 nm, while the bands at 370 and 316 nm gradually decrease generating one well defined isosbestic point at 390 nm exhibiting ∼17 fold turn-on fluorescent enhancement (FE). When we plot absorbance (at 430 nm) vs. [Zn 2+ ] there is a gradual increase in absorption with [Zn 2+ ], becoming saturated at ∼1 equivalent of Zn 2+ and then again it increases with the increase in [Zn 2+ ] and ultimately becomes saturated at ∼2 equivalents of added Zn 2+ . This clearly demonstrates that the Zn 2+ binding event to the ligand occurs in two steps, one at a time. Non-linear least-squares computer-fitting of these data gives the parameters: K ′f1 = (9.70 ± 5.51) × 10 5 M −1, n = (1.28 ± 0.05) for the first step and K ′f2 = (1.11 ± 0.65) × 10 5 M −1 and n = (1.01 ± 0.06) for the second step. So far, this study provides the opportunity where we have successfully, for the first time, determined the stepwise formation constants; though they have values of the same order of magnitude. The ground state geometries ofDFC–TS, both enol and keto forms and [Zn(DFC–TS )(OAc)], [Zn(DFC–TS )(OAc)] −, and [Zn2 (DFC–TS )(OAc)2 ] were optimized using the Gaussian-03 suit program and bond distances of all species are in reasonable agreement with the reported values.